The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/adfm.200801838
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Gold Nanoprobe Sensitive to Intracellular Reactive Oxygen Species

Abstract: Gold nanoprobes immobilized with fluorescein‐hyaluronic acid (HA) conjugates are fabricated and utilized for monitoring intracellular reactive oxygen species (ROS) generation in live cells via nanoparticle surface energy transfer. A bio‐inspired adhesive molecule, dopamine, is used to robustly end‐immobilize HA onto the surface of gold nanoparticles (AuNPs) for securing intracellular stability against glutathione. ROS induces cleavage and fragmentation of the HA chains immobilized on the surface of the AuNPs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
66
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 39 publications
3
66
1
Order By: Relevance
“…Over the last two decades, various nanomaterials including graphene oxide [1,2,3,4], Au nanoparticles [5,6,7], metal-organic framework (MOF) [8,9,10], carbon nanotubes [11,12], and MoS 2 nanosheets [13,14,15,16,17,18,19] have been synthesized to develop nanomaterial-based biosensors for a variety of applications. In particular, there has been increasing interest in developing rapid, cost-effective, and sensitive methods for DNA detection because of its vital importance in molecular diagnostics, environmental monitoring, and anti-bioterrorism [3].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, various nanomaterials including graphene oxide [1,2,3,4], Au nanoparticles [5,6,7], metal-organic framework (MOF) [8,9,10], carbon nanotubes [11,12], and MoS 2 nanosheets [13,14,15,16,17,18,19] have been synthesized to develop nanomaterial-based biosensors for a variety of applications. In particular, there has been increasing interest in developing rapid, cost-effective, and sensitive methods for DNA detection because of its vital importance in molecular diagnostics, environmental monitoring, and anti-bioterrorism [3].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, they are excellent quenchers of organic fluorophores via resonance energy transfer (RET) and can efficiently quench the molecular-excitation energy in the chromophore–AuNP composite [27]. In this sense, the quenching property of AuNPs has been employed in several chemosensing schemes [28,29], and many approaches have been used for Hg 2+ determination using AuNPs, being an area of current interest [30,31,32,33,34,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…The AuNRs, with a longitudinal absorption band at 810 nm, were prepared (Figure S2) and immobilized on the surface using a Au-catechol interaction. [26] It has been reported that the interaction force between catechol and Au is comparable to that of streptavidin and biotin. [27] The prepared PDA-RGO modified ITO surfaces (PDA-RGO/ITO) were characterized by X-ray photoelectron spectroscopy (XPS; Figure S3 a), which showed the characteristic peaks of C1s, N1s, and O1s.…”
mentioning
confidence: 98%